Peran Muhammadiyah Dalam Perubahan Sosial Masyarakat Tanjung Sakti Kabupaten Lahat Provinsi Sumatera Selatan - Abu Hanifah (Medina-te : Jurnal Studi Islam, 2021)
This research is titled the role of Muhammadiyah in the social Change Malay Society of Tanjung Sakti Kabupaten Lahat Province of South Sumatera 1930-2015. This research aims to analyze the condition of Tanjung Sakti community before Muhammadiyah stands, growth and development of Muhammadiyah, the role of Muhammadiyah on social change Tanjung Sakti, as well as the driving and inhibiting factors. This research was conducted through library research using primary and secondary data collected through literature searches and interviews. The data analysis uses descriptive qualitative, while the theories used are: theories of roles, influences, and social change. In 1930, most of the Tanjung sakti people were SinkritisMuslim, a small percentage were Catholics. And they were still underdeveloped in the fields of religion, education and social society. Based on these conditions In 1936, local merchants founded Muhammadiyah, which was engaged in the field of Islamic extermination and renewal in the field of education and social society. Until now, the movement was quite good, and the role on social change of the local community. The movement is supported by the Awakening of Religious Passion and Economic, the Openness of the Community, the Leadership System, the Human Resources and the Infrastructure as well as the Openness of Financial Management. On the other hand, this movement faces obstacles, such as the Antipathy Attitudes of the old community, the closed Attitudes of the traditional community, the Inequality Government Regulations, the Weakness of Financial Resources, and the Lack of Leaders and Ulamas.